Réponses

2013-11-13T21:09:57+01:00
E=4x² + (x+5)²
  =4x² + x² + 10x + 25
  =5x² + 10x + 25

F= -8x - (2x - 2)²
  = -8x - 2x² -8x +4
  = -2x² -16x +4

G= 5x +4(5x +4)
  = 5x +20x +16
  = 25x +16

H = 10x² -(4x+3) (4x -3)
  = 10x² -16x² +24x +9
  = -6x² +24x +9
Voilà j'espère t'avoir aider.
2013-11-13T21:15:27+01:00
5x + 3(5x+3) = 5x+15x+9 = 20x+9

4x² + (3x+4)² = 4x² + (3x+4)(3x+4) = 4x²+9x²+12x+12x+16 = 13x²+24x+16

6x² - (3x+2)(3x+2) = 6x² - (9x²+6x+6x+4) = 6x²-9x²-12x-4 = -3x²-12x-4

2x - (3x+4) (4x+3) = 2x - (12x²+9x+16x+12) = 2x-12x²-9x-16x-12 = -12x²-23x-12

4x² + (x+5)(x+5) = 4x²+x²+5x+5x+25 = 5x²+10x+25

-8x - (2x-2)² = -8x - (4x²-8x+4) = -8x-4x²+8x-4 = -4x²-4

5x+4(5x+4) = 5x+20x+16 = 25x+16

 10x² - (4x+3)(4x-3) = 10x² - (16x²-9) = -6x²+9